Progress in DNA-based heterologous prime-boost immunization strategies for malaria. - Moore, A; Hill, A (2004)
An effective vaccine against malaria is urgently required to relieve the immense human suffering and mortality caused by this parasite. A successful subunit vaccine against the liver stage of malaria will require the induction of high levels of protective T cells. Despite success in small animal models, DNA vaccines fail to induce strong cellular immune responses in humans. However, DNA vaccines can induce a T-cell response that can be strongly boosted by recombinant viral vectors. We have evaluated this heterologous prime-boost approach using the Plasmodium berghei mouse model for immunogenicity and protective efficacy against malaria challenge using combinations of plasmid DNA, recombinant modified vaccinia virus Ankara, fowlpox virus, and non-replicating adenovirus. We have proceeded to test immunogenicity and efficacy of successful heterologous prime-boost vaccines in phase I/IIa trials in malaria naïve subjects in the UK and in semi-immune individuals in The Gambia. In these clinical trials, remarkably high levels of effector T-cell responses have been induced and significant protection documented in a human sporozoite challenge model. We summarize the preclinical design and development of these heterologous prime-boost vaccines and discuss the encouraging results that have been observed in vaccinated humans.